Step-By-Step In Vitro Mutagenesis: Lessons From Fucose-Binding Lectin PA-IIL - Mrázková, Jana; Malinovská, Lenka; Wimmerová, Michaela (Methods in molecular biology (Clifton, N.J.), 2017)
Site-directed mutagenesis is a powerful technique which is used to understand the basis of interactions between proteins and their binding partners, as well as to modify these interactions. Methods of rational design that are based on detailed knowledge of the structure of a protein of interest are often used for preliminary investigations of the possible outcomes which can result from the practical application of site-directed mutagenesis. Also, random mutagenesis can be used in tandem with site-directed mutagenesis for an examination of amino acid "hotspots."Lectins are sugar-binding proteins which, among other functions, mediate the recognition of host cells by a pathogen and its adhesion to the host cell surface. Hence, lectins and their binding properties are studied and engineered using site-directed mutagenesis.In this chapter, we describe a site-directed mutagenesis method used for investigating the sugar binding pattern of the PA-IIL lectin from the pathogenic bacterium Pseudomonas aeruginosa. Moreover, procedures for the production and purification of PA-IIL mutants are described, and several basic methods for characterizing the mutants are discussed.
Keywords: Isothermal titration calorimetry (ITC); PA-IIL lectin; vazebná místa; Microscale thermophoresis; Fucose; mutageneze; bakteriální proteiny; mutageneze cílená; vazba proteinů; Bacterial Proteins; Lectins; Mutagenesis, Site-Directed; lektiny; fukosa; Surface plasmon resonance; Pseudomonas aeruginosa; Mutagenesis; Site-directed mutagenesis method; Protein crystallography; Protein Binding; Binding Sites